Optimal design and analysis of DC–DC converter with maximum power controller for stand-alone PV system. (November 2021) - Toumi, Djaafar; Benattous, Djiliani; Ibrahim, Ahmed; Abdul-Ghaffar, H.I.; Obukhov, Sergey; Aboelsaud, Raef; Labbi, Yacine; Diab, Ahmed A. Zaki
Abstract: This paper proposes a method for selecting the parameters of the main components of an autonomous photovoltaic (PV) stations to ensure the most efficient conversion and use of solar energy. The main energy characteristics are analyzed and the mathematical models of the components of an autonomous PV system are developed to study the modes of tracking the maximum power point (MPP). The necessary conditions for matching the parameters of the PV and the DC–DC buck converter are evaluated to track the MPP. This paper aims to create an original method and algorithm for calculating and selecting parameters of the main elements of a PV stations. The optimal value of the sampling time of the MPP controller is obtained for different schemes of the PV system . A practical example is considered for selecting the parameters of a DC–DC buck converter and a digital MPP of an autonomous PV station. The simulation of dynamic modes of an autonomous photovoltaic (PV) station is performed in the MATLAB/SIMULINK software package. The simulation results of dynamic operations of the PV system show that the voltage converter and the MPP controller with the selected parameters according to the proposed method provide reliable and effective tracking of the MPP in all different connections of the PV.